Kontribusi Mahasiswa Kampus Mengajar Angkatan 6 Dalam Meningkatkan Kemampuan Literasi dan Numerasi Siswa di SDN 8 Cakranegara - I Gusti Ayu Astuti Suryaningrum; Puspita Dwi Kurnia; Siti Rahmawati (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
Literacy and numeracy skills are basic competencies that every student must have in order to learn well and serve as a foundation of knowledge for learning in higher classes. Literacy skills are not limited to just the ability to read, but also include the ability to analyze a reading text and understand its meaning and concepts. Meanwhile, numeracy abilities include skills in applying mathematical concepts to solve practical problems in various situations in everyday life. The campus teaching program at elementary school 8 Cakranegara aims to help the school in the learning process, especially in the areas of literacy and numeracy. The method used in this service starts from stage (1) Pre-activity, namely debriefing; (2) Observation of placement schools; (3) Prepare an activity program design; (4) Conducting communication forums and school coordination; (5) Carry out the agreed work program and (6) Evaluate the implementation of activities. The target of this service activity is all students in elementary school 8 Cakranegara. To improve students' literacy and numeracy skills, researchers implemented several work programs, including Saturday storytelling programs, calistung tutoring, using learning media during the teaching and learning process, and implementing contextual learning. These programs have a positive impact on the school environment, especially in terms of improving the literacy and numeracy skills of students at elementary school 8 Cakranegara